PENGARUH SOSIALISASI PERPAJAKAN TERHADAP KEPATUHAN PERPAJAKAN WAJIB PAJAK USAHA MIKRO KECIL DAN MENENGAH (UMKM) DI SURAKARTA DENGAN PENGETAHUAN PERPAJAKAN SEBAGAI VARIABEL PEMEDIASI - Rizky Akbar Anwar; Muhammad Syafiqurrahman (Universitas Trunojoyo Madura, 2016)
The purpose of this study is to analyze whether tax knowledge can mediate the influence of tax socialization on tax compliance in UMKM Surakarta, and to know the influence of tax socialization on tax compliance direectly. The sampel of this research is UMKM as taxpayer listed in KPP Pratama Surakarta. The method of analysis is quantitative method using multiple linear regression analysis. Classic asumption is used to get the best model of research. Variables os research are tax socialization as independent variable, tax compliance as the dependent variable, and tax knowledge as variabe mediation. The result of research indicate that tax socialization has positive influence tax significantly on tax knowledge and tax compliance. Tax knowledge has positive influence significantly on tax compliance, and mediate influence of tax socialization on tax compliance for UMKM taxpayer in Surakarta.